Test case generator based on UML activity diagram - Loh, Kha Bee (2014)
Software testing serves to identify and report bugs exist in system. Test case is required to aid the process of testing by giving the event that can and should be verified. Nowadays, there are testing tool that required tester to enter system execution script. This can affect the quality of test due to lack of experience of tester or human mistakes. In this project, test case generator based on Unified Modeling Language (UML) Activity Diagram is developed. With generating of flow graph from UML Activity Diagram, test cases are able to be output. Therefore, the test case number of particular UML Activity Diagram can be determined.